Activating human genes with zinc finger proteins, transcription activator-like effectors and CRISPR/Cas9 for gene therapy and regenerative medicine. (August 2014) - Gersbach, Charles A; Perez-Pinera, Pablo
<x xml:space="preserve">Abstract</x> New technologies have recently been developed to control the expression of human genes in their native genomic context by engineering synthetic transcription factors that can be targeted to any DNA sequence. The ability to precisely regulate any gene as it occurs naturally in the genome provides a means to address a variety of diseases and disorders. This approach also circumvents some of the traditional challenges of gene therapy. In this editorial, we review the technologies that have enabled targeted human gene activation, including the engineering of transcription factors based on zinc finger proteins, transcription activator-like effectors and the CRISPR/Cas9 system. Additionally, we highlight examples in which these methods have been developed for therapeutic applications and discuss challenges and opportunities.